2007
DOI: 10.1206/0003-0082(2007)3591[1:ttdmcm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Trilobite “Dalmanites” Maecurua Clarke, 1890 (Middle Devonian, Amazon Basin, Brazil) and the New Genus Amazonaspis (Synphoriidae)

Abstract: The revision of "Dalmanites" maecurua Clarke, 1890, from the Upper Lontra Member, Eifelian, Maecuru Formation, Para State, Amazon Basin, Brazil is presented. The new genus Amazonaspis is assigned within the family Synphoriidae. Comparisons are made with other Silurian and Devonian synphoriids, and some paleobiogeographic inferences are presented. RESUMO E apresentada a revisao de "Dalmanites" maecurua Clarke, 1890, procedente da parte superior do Membro Lontra, Eifeliano, da Formagao Maecuru, no estado do Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 15 publications
0
20
0
4
Order By: Relevance
“…Genera assigned. Synphoria Clarke, 1894; Amazonaspis Carvalho and Fonseca, 2007; Anchiopsis Delo, 1935; Chacomurus Braniša and Vaněk, 1973; Coronura Hall and Clarke, 1888; Dalmanitoides Delo, 1935; Delops Rickards, 1965; Fenestraspis Braniša and Vaněk, 1973; Lygdozoon Holloway, 1981; Odontocephalus Conrad, 1840; Schoharia Lespérance, 1975; Synphoroides Delo, 1940; and Trypaulites Delo, 1935.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genera assigned. Synphoria Clarke, 1894; Amazonaspis Carvalho and Fonseca, 2007; Anchiopsis Delo, 1935; Chacomurus Braniša and Vaněk, 1973; Coronura Hall and Clarke, 1888; Dalmanitoides Delo, 1935; Delops Rickards, 1965; Fenestraspis Braniša and Vaněk, 1973; Lygdozoon Holloway, 1981; Odontocephalus Conrad, 1840; Schoharia Lespérance, 1975; Synphoroides Delo, 1940; and Trypaulites Delo, 1935.…”
mentioning
confidence: 99%
“…Braniša and Vaněk (1973, p. 99) suggested that ‘ Dalmanites ’ maecurua Clarke, 1890, from the upper part of the Maecuru Formation (Eifelian) of Brazil, may belong to Fenestraspis . This species was revised by Carvalho and Fonseca (2007) who assigned it to their new genus Amazonaspis . In addition to lacking thoracic and pygidial fenestrae, Amazonaspis differs from Fenestraspis in many other characters.…”
mentioning
confidence: 99%
“…Na Bacia do Amazonas, os trilobitas devonianos compõem-se de representantes recentemente revisados (e.g., Amazonaspis maecurua, Carvalho & Fonseca, 2007; Digonus derbyi, Carvalho & Ponciano, 2015), com a nomenclatura em aberto (e.g., Phacops? pullinus, Clarke, 1890;Tarijactinoides?…”
Section: Problemática Envolvidaunclassified
“…Trabalhos mais recentes (e.g. Carvalho & Fonseca, 2007) (Morzadec et al, 2015), localidade esta que faz parte da Subprovíncia Colombiana do Domínio das Américas Orientais (Boucot, 1988 (Fonseca, 2015).…”
Section: Revisão Sistemática (Anexos II Iii Iv V E Vi)unclassified
See 1 more Smart Citation